Recent status and trends regarding oxidative stress in gliomas (2013 - 2025): a systematic review and bibliometric analysis - Zeng, Yijun; Lu, Xiaowen; Wang, Yadan; He, Jihong; Cao, Hui; Zhang, Lushun; Cheng, Li (Frontiers in Oncology, 2025)
BackgroundGlioma, a prevalent brain tumor originating from glial cells, exhibits rapid growth, high recurrence, and significant invasiveness. Standard treatments include surgery, radiotherapy, and chemotherapy, yet their effectiveness remains unsatisfactory. Recent studies implicate oxidative stress in promoting glioma cell proliferation and migration, as well as enhancing survival rates, suggesting antioxidant therapy as a potential tumor treatment strategy.ObjectiveThe aim of this review is to summarize the research hotspots on antioxidant treatment options for gliomas in the last twelve years and analyze the future trends through bibliometric analysis.MethodWe collected articles on oxidative stress in gliomas published between January 1, 2013, and April 5, 2025, using the Web of Science (WOS) database. We also visualized and analyzed annual publications, countries, and journals using VOSviewer, Citespace, and pajek.ResultThe search yielded a total of 1020 publications. Visual analyses show that the number of articles on this topic has increased annually over the last twelve years. Most of the studies came from China, followed by the United States. The three most cited journals were International Journal of Molecular Sciences, Cancer and Frontiers in Oncology. The author who published the most articles on this topic was Wang HD.ConclusionThrough a systematic analysis, we found that current research hotspots mainly focus on the dose of reactive oxygen species (ROS) and tumor proliferation, inflammatory response, apoptosis, etc. in relation to oxidative stress. In addition, we analyzed the direction of future research: a possible focus on the treatment of gliomas via ‘tumor microenvironment’, ‘blood-brain barrier’, ‘anti-inflammatory’ and ‘ ferroptosis induction ‘ routes.